Analysis of current data on the use of topical mTOR inhibitors in the treatment of facial angiofibromas in tuberous sclerosis complex—An update. (5th November 2022) - Balestri, Riccardo; Rizzoli, Laura; Pedrolli, Annalisa; Urru, Silvana Anna Maria; Rech, Giulia; Neri, Iria; Girardelli, Carlo R.; Magnano, Michela
Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant neurocutaneous syndrome causing hamartomatous growths in multiple organs. Facial angiofibromas occur in up to 80% of patients and can be highly disfiguring. Treatment for these lesions is challenging. Recently, topical rapamycin has been proposed as an effective option to treat angiofibromas but a commercially available compound has not yet been developed in Europe. We conducted a retrospective review with the aim to update the current data on the use of topical rapamycin in the treatment of angiofibromas in TSC, focusing on the optimal concentration and trying to establish which vehicle should be preferred. Thirty‐nine reports describing the use of topical rapamycin in the treatment of angiofibromas in TSC were considered, involving a total of 483 patients. An improvement of the lesions has been shown in over 90% of subjects, particularly if the treatment was started at early stages. Several different formulations (ointment, gel, solution and cream) with a wide range of concentrations (0.003%–1%) were proposed, of which a pharmacological analysis has also been performed. Topical rapamycin can be considered an effective and safe option for the treatment and the prevention of facial angiofibromas in younger patients, but the best formulation has yet to be established. Our review demonstrates that ointment and gel should be preferred, but it is not clear which concentration is optimal. However, according to this study, the 0.1% concentration represents the first choice. Long‐term and comparative studies between topical rapamycin formulations are required in order to establish which treatment has a better outcome and lower recurrence rate.